2017
DOI: 10.1136/bjophthalmol-2017-310719
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal imaging of small hard retinal drusen in young healthy adults

Abstract: BackgroundSmall hard macular drusen can be observed in the retina of adults as young as 18 years of age. Here, we seek to describe the in vivo topography and geometry of these drusen.MethodsRetinal images were acquired in young, healthy adults using colour fundus photography, spectral domain optic coherence tomography (SD-OCT), reflectance flood-illuminated adaptive optic ophthalmoscopy (AO flood) and reflectance adaptive optic scanning light ophthalmoscopy (AOSLO) in both confocal and non-confocal split-detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 32 publications
0
15
0
1
Order By: Relevance
“…1 Small hard drusen within the macula have been observed in 22% of 97 healthy young adults in Norway with a mean age of 23 years. 22 We found that the risk of having small hard drusen outside the macula increased nearly four times when drusen were present in the macula. This is an interesting corollary to studies of early 6 and late 23,24 AMD, which have shown a similar association between macular and extramacular lesions.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…1 Small hard drusen within the macula have been observed in 22% of 97 healthy young adults in Norway with a mean age of 23 years. 22 We found that the risk of having small hard drusen outside the macula increased nearly four times when drusen were present in the macula. This is an interesting corollary to studies of early 6 and late 23,24 AMD, which have shown a similar association between macular and extramacular lesions.…”
Section: Discussionmentioning
confidence: 67%
“…38 The strengths of the present study included its populationbased design, the high number of participants, and the inclusion of OCT, even if it was not invariably applied in a mode that is optimal for the imaging of small hard drusen. Specifically, the scan locations were not customized to the actual small hard drusen seen in a given participant and even if they had been, small hard drusen are not invariably visible on OCT. 22 The examination of the relation between small hard drusen and choroidal thickness was a preplanned but secondary analysis. As such, there is a risk of mass significance resulting from multiple testing and therefore replication in one or more separate studies is desirable.…”
Section: Discussionmentioning
confidence: 99%
“…The Kongsberg AOSLO 27,28 was used to obtain images of the photoreceptor mosaic in five participants with aniridia (4 males, aged 40-66 yrs), and 30 age-matched normal controls including four unaffected family members. Ocular media opacities and nystagmus precluded imaging of the photoreceptor mosaic in participant 5114 and 5135.…”
Section: Adaptive Optics Scanning Light Ophthalmoscopymentioning
confidence: 99%
“…Image analyses and registration was performed as described previously. 28 Registered images from each retinal location were manually stitched together into a montage aligned with the corresponding en-face infrared image acquired by the OCT using selected blood vessel landmarks. These steps ensured that the AOSLO images were correctly scaled and positioned irrespective of the individual subject's fixation skill and uncontrolled eye movements.…”
Section: Adaptive Optics Scanning Light Ophthalmoscopymentioning
confidence: 99%
“…W badanym materiale klinicznym druzy twarde rozpoznano u 22,6% chorych.Druzy twarde to najczęściej druzy o średnicy małej (poniżej 63 µm), rzadziej średniej (64-125 µm)(13,14). W obrazie oftalmoskopowym (ryc.…”
unclassified